Delineation of structural and tectonic features in the Mahanadi basin, eastern India: New insights from remote sensing and land gravity data. (15th April 2022) - Satyakumar, Animireddi V.; Pandey, Anand K.; Singh, Anand P.; Tiwari, Virendra M.
Graphical abstract: Highlights: An integrated analysis (ALOS PALSAR, SRTM-DEM, and Ground Gravity data) is performed to delineate the structural and tectonic framework at the Mahanadi graben, India. The 2-D gravity model incorporates the rifting model of the basin formation along the preexisting basement shear zones. The structural trends with pronounced geomorphic expressions represent the reactivated structures formed under the evolving stress regimes of the Mahanadi graben. Abstract: During Gondwana dispersal, the Mahanadi basin experienced rifting and reactivation of preexisting structures, causing terrain deformation with faulting. The landform around Proterozoic Sukinda Thrust in the Mahanadi basin provides an opportunity to map the geomorphic expressions and correlate them with the tectonics of the graben using remote sensing images, digital elevation model, and gravity data. The subsurface extensions of the identified structures using SAR data and relief image analysis are modeled with the Bouguer gravity anomaly. The mapped tectonic features correlate well with the gravity gradient trends in residual gravity anomalies. The E-W and NW-SE trending residual gravity lineaments match well with the mapped faults and suggest their extension within the shallow crust. The two-dimensional (2-D) gravity model realistically constrains the subsurface geology, and by incorporating other published data, we suggest that the Gondwana rifting had reactivated the preexisting shear zones in the cratonic basement down to a depth of ∼ 5 km and subsequently deposited sediments into the fault-bound shallow basin of the Mahanadi graben.